ANALISIS BIBLIOMETRIKA PADA ARTIKEL JURNAL PSIKODIMENSIA TAHUN 2018-2022 DENGAN VISUALISASI MENGGUNAKAN SOFTWARE VOSVIEWER - Adirati, Melania; Susianti, Vivi Aprillia; Ananda, Angelia Selma (Jurnal Pustaka Budaya, 2023)
This study discusses the bibliometric mapping of scientific publications in the Journal of Pikodimensia for the period of 2018 to 2022, using VOSviewer software. The aim of this study is to determine author productivity, author collaboration patterns, research topic development based on keywords, and the development of collaborative networks among authors. The method used in this study is a qualitative descriptive approach with bibliometric analysis using VOSviewer. The results of this study indicate that collaboratively written articles are more common than individual articles. Nine authors were found to collaborate with each other, while the two most productive authors were Lucia Hernawati and Jemerson Naceno Domiguez. In addition, the keywords that frequently appear in the abstracts are Covid-19 and resilience